Del “momento mexicano” a la realidad de la violencia político – criminal - Serrano, Mónica (El Colegio de México A.C., 2020)
In order to examine the legacy of insecurity and violence left by Enrique Peña Nieto’s term in office in the context of multiple crisis, this paper begins with the relationship between democratization and security in the context of the political transition, together with the recent history of the country. Analysis of the profile of victims of criminal violence not only allows us to identify its discriminatory nature, but to reach into its underlying logic. In addition to identifying drugs trafficking and organized crime as drivers of this violence, the study also examines its effects on the Mexican state. The final section of the text looks at the humanitarian tragedy that emerged from this legacy together with its domestic and international repercussions, before evaluating the various consequences for Mexico.